Transcriptome analyses of adult mouse brain reveal enrichment of lncRNAs in specific brain regions and neuronal populations - Kadakkuzha, Beena M.; Liu, Xin-An; McCrate, Jennifer; Shankar, Gautam; Rizzo, Valerio; Afinogenova, Alina; Young, Brandon; Fallahi, Mohammad; Carvalloza, Anthony C.; Raveendra, Bindu; Puthanveettil, Sathyanarayanan V. (Frontiers in Cellular Neuroscience, 2015)
Despite the importance of the long noncoding RNAs (lncRNAs) in regulating biological functions, the expression profiles of lncRNAs in the sub-regions of the mammalian brain and neuronal populations remain largely uncharacterized. By analyzing RNASeq datasets, we demonstrate region specific enrichment of populations of lncRNAs and mRNAs in the mouse hippocampus and prefrontal cortex (PFC), the two major regions of the brain involved in memory storage and neuropsychiatric disorders. We identified 2,759 lncRNAs and 17,859 mRNAs in the hippocampus and 2561 lncRNAs and 17,464 mRNAs expressed in the PFC. The lncRNAs identified correspond to ~14% of the transcriptome of the hippocampus and PFC and ~70% of the lncRNAs annotated in the mouse genome (NCBIM37) and are localized along the chromosomes as varying numbers of clusters. Importantly, we also found that few of the tested lncRNA-mRNA pairs that share a genomic locus display specific co-expression in a region-specific manner. Furthermore, we find that sub-regions of the brain and specific neuronal populations have characteristic lncRNA expression signatures. These results reveal an unexpected complexity of the lncRNA expression in the mouse brain.